ANALISIS BUSINESS MODEL CANVAS DAN VALUE PROPOSITION CANVAS SEBAGAI STRATEGI PENGEMBANGAN USAHA BISNIS MAKANAN SEHAT PASCA PANDEMI COVID-19 - Nur Afidah (Komunitas Dosen Indonesia, 2024)
As the pandemic COVID-19 comes to an end, there have been changes in shopping methods and food preferences among the public. Offline shopping has resumed, and there is a wider variety of food choices available. Asinan Niekting, a culinary SME, is one of those that survived during the pandemic experiencing the decline of sales after the pandemic. Their products, which offer numerous health benefits, became popular choices for personal consumption and for sending to those in isolation not performed well as the during pandemic era due to the awareness of healthy eating that has been somewhat overshadowed by the abundance of food options in public places like malls, culinary centres, and markets as the offline shopping methods back to normal. Therefore, the objective of this research is to provide a business development strategy for Asinan Niekting to be sustain in the post-pandemic era. The method used is qualitative descriptive, including in-depth interviews, observation, and performance analysis through internal sales data. Data were collected through structured interviews with the business owner and customers of Asinan Niekting, as well as online observation to capture daily interactions and operational practices. The collected data analyzed using two tools, the value proposition canvas and the business model canvas. To create the business model canvas, we start with the customer segment and value proposition that we formulated in the proposition map of the value proposition canvas. The research findings indicate that there are customer pains that have not been addressed by the product’s value as a pain reliever, such as not knowing where to buy the product, the distance of the seller, and the lack of freshness. The product also still needs gain creators for customer gains that being easily accessible and enjoyable with family. From these findings, it can be concluded that there are rooms for improvement in current Business Model Canvas Asinan Niekting. specifically in the areas of channel, key partnership, key resources, and cost structure. Therefore, the recommended strategy for Asinan Niekting includes expanding sales through offline stores, retail outlets, food delivery apps like GoFood, GrabFood, ShopeeFood, and Maxim, as well as through e-commerce platforms like Shopee and Tokopedia.